2001
DOI: 10.1016/s0364-0213(01)00044-1
|View full text |Cite
|
Sign up to set email alerts
|

Learning from human tutoring

Abstract: Human one-to-one tutoring has been shown to be a very effective form of instruction. Three contrasting hypotheses, a tutor-centered one, a student-centered one, and an interactive one could all potentially explain the effectiveness of tutoring. To test these hypotheses, analyses focused not only on the effectiveness of the tutors' moves, but also on the effectiveness of the students' construction on learning, as well as their interaction. The interaction hypothesis is further tested in the second study by mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
122
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(139 citation statements)
references
References 38 publications
14
122
2
1
Order By: Relevance
“…It was expected that the intervention would enhance students' conceptual understanding of the subject matter, because students would be provoked to focus on and actively think about the subject matter. Several studies have shown these positive effects of asking questions (Chi, Siler, Jeong, Yamauchi, & Hausman, 2001;Glaser, 1991;Graesser, Baggett, & Williams, 1996;Graesser, Person, & Magliano, 1995). The guiding questions also had a metacognitive component, because the students became more aware of their own learning (Boekaerts, 1997;Schraw, Crippen, & Hartley, 2006;Veenman, Van Hout-Wolters, & Afflerbach, 2006).…”
Section: Directive Tutor Guidancementioning
confidence: 99%
“…It was expected that the intervention would enhance students' conceptual understanding of the subject matter, because students would be provoked to focus on and actively think about the subject matter. Several studies have shown these positive effects of asking questions (Chi, Siler, Jeong, Yamauchi, & Hausman, 2001;Glaser, 1991;Graesser, Baggett, & Williams, 1996;Graesser, Person, & Magliano, 1995). The guiding questions also had a metacognitive component, because the students became more aware of their own learning (Boekaerts, 1997;Schraw, Crippen, & Hartley, 2006;Veenman, Van Hout-Wolters, & Afflerbach, 2006).…”
Section: Directive Tutor Guidancementioning
confidence: 99%
“…Stimulating or prompting self-explanations increases cognitive activity. Relevant cognitive activity promotes the construction of coherent knowledge structures, which enhances understanding of the subject matter and performance of the learner (Chi, 1996;Chi, Siler, Jeong, Yamauchi, & Hausman, 2001). Such relevant cognitive activity increases germane CL and can only be accomplished when the total CL does not lead to an overload of the limited cognitive system.…”
Section: Self-explanationsmentioning
confidence: 99%
“…Human tutors can also guide student reasoning. By means of successive dialogue exchanges between the tutor and the students, and by focussing students' attention, the tutor can scaffold the construction of self-explanations, which in turn promotes learning (Chi, 1996;Chi et al, 2001;Merrill, Reiser, Merrill, & Landes, 1995;Merrill, Reiser, Ranney, & Trafton, 1992). The intervention with the directive questions mimicked human tutors who guide student reasoning, because it focused students' attention and was expected to elicit self-explanations.…”
Section: Guidancementioning
confidence: 99%
“…PBL is widely used worldwide in higher education, particularly in medical education. The causes of this efficacy pertaining to the interaction are still intricate and can involve the tutor's initiative, the learners' initiative, or their joint initiative (Chi, Siler, Jeong, Yamauchi, & Hausmann, 2001). Answers to a vast quantity of critical questions including the following cannot be obtained by relying only on conversational data: How accurate is the teacher monitoring of students' learning state?…”
Section: An Example Of a Study: A Teacher Coaching A Student In Classmentioning
confidence: 99%